2015
DOI: 10.1016/j.nano.2014.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic composition of single nano-sized extracellular blood vesicles

Abstract: Extracellular vesicles (EVs) are important in normal physiology and are altered in various pathologies. EVs produced by different cells are antigenically different. Since the majority of EVs are too small for routine flow cytometry, EV composition is studied predominantly in bulk, thus not addressing their antigenic heterogeneity. Here, we describe a nanoparticle-based technique for analyzing antigens on single nano-sized EVs. The technique consists of immuno-capturing of EVs with 15-nm magnetic nanoparticles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 46 publications
3
38
0
1
Order By: Relevance
“…Earlier we demonstrated that the efficiency of our technique for capture of viruses and EVs of interest is about 99% [25,30]. In the current work we confirmed this result: we captured EVs via MNP-coupled antibodies against CD41a, stained them with antibodies against CD31 and CD63 and isolated on magnetic columns.…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…Earlier we demonstrated that the efficiency of our technique for capture of viruses and EVs of interest is about 99% [25,30]. In the current work we confirmed this result: we captured EVs via MNP-coupled antibodies against CD41a, stained them with antibodies against CD31 and CD63 and isolated on magnetic columns.…”
Section: Methodssupporting
confidence: 85%
“…Here, we attempted to trace the origin of EVs by determining the antigenic composition of individual EVs isolated from blood of healthy volunteers and from blood of patients with acute forms of coronary artery disease, in particular myocardial infarction. This task was accomplished with the new technology “flow virometry”, which was originally developed for the analysis of individual virions [30] and later adapted to analyze individual small EVs [25]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recent developments in flow cytometrybased techniques have opened up the possibility to quantify and characterize particles 50-200 nm in size. Such developments include not only hardware adaptations in high-end flow cytometers to improve signal-to-noise ratios, but also optimized staining protocols for general labeling of EVs and the use of magnetic nanoparticles to screen the surface antigenic composition of EVs (47,48).…”
Section: Mission (mentioning
confidence: 99%
“…However, for diagnostic purposes such an approach will require screening of large amounts of vesicles as 'diseased' EVs are rare among the total isolated EV population. One promising approach relies on modifying flow cytometry equipment/protocols to detect single, nanosized EVs [244][245][246]. However, to date FACS is not able to detect the lower size range of EVs and requires antibodies (and hence also knowledge of a particular disease marker) to phenotype EVs.…”
Section: 2evs As Biomarkermentioning
confidence: 99%